The Implementation of Islamic Religious Education with A Multicultural Perspective at SMA Piri 1 Yogyakarta - Asroni, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research article discusses the implementation of Islamic Religious Education (hereafter abbreviated as IRE) with a multicultural perspective at the High School (SMA) of PIRI 1 Yogyakarta. This study is field research with a qualitative approach. The data were collected through observation, documentation, and interviews. The results of this study indicated that: First, IRE learning at SMA PIRI 1 Yogyakarta has matched the criteria of IRE with a multicultural perspective because SMA PIRI 1 Yogyakarta has: (1) created a diverse academic environment; (2) engaged multicultural IRE’s teachers; (3) made IRE learning fun, inclusive, and inspiring. Second, IRE learning with a multicultural perspective taught at SMA PIRI 1 Yogyakarta can change students. This change involves their mindset and understanding of students and students' behavior towards different Islamic groups and followers of other religions. Another finding was that teaching IRE at SMA PIRI 1 Yogyakarta applied a principle of rahmatan lil alamin, which was illustrated by the teacher’s behavior and the diversity in teaching staff in the school. Last but not least, this is quite different from learning in the past, in which they were unfairly prejudiced against followers of other religions.